Noninvasive estimation of fibrosis progression overtime using the FIB‐4 index in chronic hepatitis C. Issue 1 (4th July 2012) - Tamaki, N.; Kurosaki, M.; Tanaka, K.; Suzuki, Y.; Hoshioka, Y.; Kato, T.; Yasui, Y.; Hosokawa, T.; Ueda, K.; Tsuchiya, K.; Nakanishi, H.; Itakura, J.; et al.
<x xml:space="preserve">Abstract</x> Summary. The FIB‐4 index is a simple formula to predict liver fibrosis based on the standard biochemical values (AST, ALT and platelet count) and age. We here investigated the utility of the index for noninvasive prediction of progression in liver fibrosis. The time‐course alteration in the liver fibrosis stage between paired liver biopsies and the FIB‐4 index was examined in 314 patients with chronic hepatitis C. The average interval between liver biopsies was 4.9 years. The cases that showed a time‐course improvement in the fibrosis stage exhibited a decrease in the FIB‐4 index, and those that showed deterioration in the fibrosis stage exhibited an increase in the FIB‐4 index with a significant correlation (P < 0.001). Increase in the ΔFIB‐4 index per year was an independent predictive factor for the progression in liver fibrosis with an odds ratio of 3.90 (P = 0.03). The area under the receiver operating characteristic curve of the ΔFIB‐4 index/year for the prediction of advancement to cirrhosis was 0.910. Using a cut‐off value of the ΔFIB‐4 index/year <0.4 or ≥0.4, the cumulative incidence of fibrosis progression to cirrhosis at 5 and 10 years was 34% and 59%, respectively in patients with the ΔFIB‐4 index/year ≥0.4, whereas it was 0% and 3% in those with the ΔFIB‐4 index/year <0.4 (P < 0.001). In conclusion, measurement of the time‐course changes in the FIB‐4 index is useful for the noninvasive and real‐time estimation of the progression in liver fibrosis.